Improvement in the Performance of Inverted 3D/2D Perovskite Solar Cells by Ambient Exposure. Issue 7 (12th April 2022) - Wang, Yantao; Lin, Jingyang; He, Yanling; Zhang, Yi; Liang, Qiong; Liu, Fangzhou; Zhou, Zhiwei; Chan, Christopher C. S.; Li, Gang; Feng, Shien-Ping; Ng, Alan Man Ching; Wong, Kam Sing; et al.
Abstract : Perovskite solar cells (PSCs) are known to be sensitive to the exposure to ambient humidity, which typically results in the degradation and deterioration of performance, although positive effects of exposure to moisture have also been reported, due to recrystallization of the perovskite. Common approach to improve stability is to use 3D/2D perovskite active layer, where 2D capping layer is prepared by spin coating the bulky organic cation halide. Herein, it is shown that optimizing the exposure of the capping layer prepared by spin coating phenylethylammonium iodide (PEAI) to ambient atmosphere results in substantial improvement of the PSC performance. Furthermore, the initial effects of PEAI treatment are dependent on the NiO x /perovskite interface, but in all cases except at very high humidity (80–85% RH) optimized exposure to ambient results in improved performance. The variations in device performance with PEAI treatment and ambient exposure can be attributed to defect passivation and changes in the charge extraction due to energy‐level alignment at the interfaces. The best performing devices have passivation of NiO x /perovskite interface and PEAI treatment of top surface followed by exposure to ambient atmosphere at RH of 40–45%, which results in the power conversion efficiency increase from 20.3% to 22.4%. Abstract : Phenylethylammonium iodide (PEAI) treatment results in the formation of 2D PEA2 PbI4 capping layer on 3D perovskite which passivates defects and increases hydrophobicity, but hinders electron collection. The ambient exposure downshifts energy levels facilitating charge collection, improving efficiency and stability. Energy‐level alignment with PEAI treatment is also affected by hole transport layer (HTL)/perovskite interface modification, which facilitates favorable alignment with PEA2 PbI4 .